2012
DOI: 10.1007/s00442-012-2259-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tree species diversity on fine-root production in a young temperate forest

Abstract: The phenomenon of overyielding in species-diverse plant communities is mainly attributed to complementary resource use. Vertical niche differentiation belowground might be one potential mechanism for such complementarity. However, most studies that have analysed the diversity/productivity relationship and belowground niche differentiation have done so for fully occupied sites, not very young tree communities that are in the process of occupying belowground space. Here we used a 5–6 year old forest diversity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 58 publications
0
57
1
3
Order By: Relevance
“…Therefore our findings also do not conform to those of a previous study in boreal North America where fine root biomass responded positively to tree species diversity in mature forests consisting of mixtures of conifers and broadleaf species (Brassard et al, 2011), but agree more with studies conducted in young temperate broadleaf-conifer plantations where tree or ground vegetation fine root biomass did not differ between monocultures and 2-4 species mixtures (Lei et al, 2012b, Domisch et al, 2015. Our forest stands were middleaged forests, and earlier the positive diversity effect on both on aboveground (Zhang et al, 2012) and fine root productivity has been proposed to be more distinct in middle-aged forests than in young forests (Ma and Chen, 2017).…”
Section: Diversity Effects On Fine Root Biomasscontrasting
confidence: 39%
See 1 more Smart Citation
“…Therefore our findings also do not conform to those of a previous study in boreal North America where fine root biomass responded positively to tree species diversity in mature forests consisting of mixtures of conifers and broadleaf species (Brassard et al, 2011), but agree more with studies conducted in young temperate broadleaf-conifer plantations where tree or ground vegetation fine root biomass did not differ between monocultures and 2-4 species mixtures (Lei et al, 2012b, Domisch et al, 2015. Our forest stands were middleaged forests, and earlier the positive diversity effect on both on aboveground (Zhang et al, 2012) and fine root productivity has been proposed to be more distinct in middle-aged forests than in young forests (Ma and Chen, 2017).…”
Section: Diversity Effects On Fine Root Biomasscontrasting
confidence: 39%
“…Reported relationships were positive (Schmid, 2002;Meinen et al, 2009a;Brassard et al, 2011, Brassard et al, 2013Laclau et al, 2013;Bu et al, 2017;Ma and Chen, 2017;Sun et al, 2017), insignificant (Hendricks and Bianchi, 1995;Schmid and Kazda, 2002;Bauhus et al, 2000;Meinen et al, 2009b, Meinen et al, 2009cJacob et al, 2010, Jacob et al, 2013Brassard et al, 2013;Lei et al, 2012b;Domisch et al, 2015;Ma and Chen, 2017) or negative (Bolte and Villanueva, 2006). The more numerous studies between tree species diversity and above-ground biomass and biomass production of trees show more consistent positive diversity effects (Zhang et al, 2012;Gamfeldt et al, 2013;Vilà et al, 2013;Ratcliffe et al, 2015;Toïgo et al, 2015;Wu et al, 2015;Jucker et al, 2016;Liang et al, 2016;Pretsch and Schütze, 2016), suggesting that tree species diversity effects on above-ground biomass or productivity are not necessarily mirrored by tree fine root productivity (Bauhus et al, 2000;Chen and Klinka, 2003;Brassard et al, 2011;Lei et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Fine roots in mixed stands compared with pure stands are always assumed to exploit deeper soil (Cremer et al, 2016), so they may assemble more nitrogen from deeper soil (even deeper than our samples) to upper soil. Also, Lei et al (2012b) reported higher fine-root turnover caused by higher fine-root production of mixed stands, which potentially increases nitrogen input in mixed stands. In addition, mixed stands are more resistant to environmental disturbances, are more capable of N retention and prevent leaching in soil (Tilman et al, 1996).…”
Section: Admixing Effect Along the Chronosequencementioning
confidence: 98%
“…Vehviläinen et al 2007;Bolte et al 2009;Richards et al 2010;Lei et al 2012;Hantsch et al 2013;Forrester et al 2014;Forrester 2014b;Pollastrini et al 2014;Collet et al 2014). In addition, Pretzsch (2013) found that some species mixtures had positive effects in older stands.…”
Section: Tree Sizes and Agementioning
confidence: 98%